Developing the workforce: Exploring the impact of female directors on male-led new ventures - Wu, Zhiyan; Naldi, Lucia (Journal of Business Venturing, 2025)
This study investigates whether and how female directors influence the performance of male-led new ventures. Guided by resource dependence theory, which sees boards as providers of key resources and advice, we shift the focus adopted in prior research on female directors' strategic roles in public firms to argue that, in male-led new ventures, their influence is more operationally focused. Using data from Sweden and an instrumental variable approach that exploits the random assignment of a child's sex at birth among male founders, we find that greater female board representation is positively associated with the performance of male-led new ventures. Further analyses suggest this effect operates primarily through workforce development—namely, the hiring of skilled female employees and the provision of competitive compensation. Notably, even a single female director has a measurable impact. This study underscores the distinct role of female directors in entrepreneurial settings as opposed to established firms, illuminating the mechanisms through which female presence in the boardroom positively affects the early life stages of organizations. We hope our research serves as a basis for future research to explore further the roles played by female directors that are particularly relevant at the startup stage.